Iron Deficiency in Heart Failure: Pathophysiology, Diagnosis, and Therapeutic Strategies – A Narrative Review - Jurkowski, Filip; Sito, Maksymilian; Marczak, Zuzanna; Wójcik, Łukasz; Gawron, Natalia; Bojanowski, Hubert Tomasz; Dobracka, Aleksandra; Zachar, Kinga; Jarowicz, Monika; Czmyr, Jędrzej (Journal of Education, Health and Sport, 2026)
Introduction and Purpose: Heart failure (HF) imposes a significant global burden. Iron deficiency (ID) constitutes a prevalent comorbidity affecting up to 50% of patients, independently worsening prognosis regardless of anemia status. This review analyzes the pathophysiology of ID, specifically impaired myocardial energetics, clarifies diagnostic criteria, and compares the efficacy of oral versus intravenous therapeutic strategies. A comprehensive literature search was conducted using PubMed, Scopus, and Embase (2015–2026). The review focuses on landmark randomized trials (AFFIRM-AHF, IRONMAN, HEART-FID), recent meta-analyses, and current international guidelines . State of knowledge: ID impairs mitochondrial oxidative phosphorylation and myocardial contractility. In HF, chronic inflammation may upregulate hepcidin, which induces the internalization and degradation of ferroportin, blocking intestinal iron absorption. Consequently, evidence from randomized trials suggests that oral iron supplementation has not demonstrated consistent clinical benefit in repleting iron stores or improving functional capacity in patients with heart failure. In contrast, intravenous iron formulations (ferric carboxymaltose, ferric derisomaltose) bypass these regulatory barriers. Evidence indicates that intravenous repletion significantly improves exercise capacity and quality of life, and reduces the risk of recurrent HF hospitalizations. Summary: Assessment of iron status using serum ferritin and transferrin saturation is a vital aspect of modern heart failure management. Due to physiological absorption barriers and systemic inflammation, oral iron supplementation has not demonstrated consistent clinical benefit in this population. Current evidence supports intravenous iron repletion as an effective, evidence-based strategy for improving symptoms and reducing the risk of hospitalizations, specifically in symptomatic patients with HFrEF or HFmrEF and concomitant iron deficiency.